Paying for digital information: Assessing farmers’ willingness to pay for a digital agriculture and nutrition service in Ghana - Hidrobo, Melissa; Palloni, Giordano; Aker, Jenny C.; Gilligan, Daniel O.; Ledlie, Natasha (International Food Policy Research Institute, 2020)
With the widespread growth of mobile phone coverage and adoption over the past decade, there has been considerable enthusiasm over the potential for information and communication technologies (ICTs) to provide a low-cost approach for farmers to overcome information constraints in agricultural initiatives. The commercial viability of ICTs relies on effective demand for these services. This paper assesses farmers’ willingness to pay (WTP) for a digital platform that provides nutrition-sensitive agricultural information in Ghana. Using the Becker-DeGroot-Marschak method to elicit WTP, we randomly vary the framing of the marketing messages for the service, as well as the gender of the person targeted, to examine the effects of framing and respondent gender on demand. We find that farmers are highly price sensitive, but most are willing to pay a low monthly price for the service. A nutrition-focused marketing message leads to higher WTP than an agriculture only message, and women have substantially lower WTP than men, with the latter difference driven by lower WTP for the service among women who report access to alternative sources of nutrition, health, and agriculture information.